Rapid atraumatic sex identification of developmental day 14–16 mice. (May 2015) - Song, J; Song, J; Xue, K; Han, H; Ding, F; Li, S; Dai, Y; Li, N
Abstract Embryonic mice have been used widely to study organ development. Days 14–16 are critical for sex organ development and differentiation in mice. Current methods for sex identification are limited. Even the simplest polymerase chain reaction method may injure the embryo. We determined that morphologic analysis of embryonic mammary anlagen could be used for rapid atraumatic sex identification of day 14–16 mice. The accuracy of our method was verified by molecular and anatomical approaches.